Making Sense of the Yoruba Littoral - Ayodeji Olukoju (Yoruba Studies Review)
This article examines the Yoruba coast in its local and global settings. Drawing on the work by Michael Pearson, the article argues that the Yoruba littoral is by no means a monolithic community in cultural, religious and economic terms. It points out that while most Yoruba define themselves in relation to fixed settlements in the hinterland, the littoral is defined by high mobility and flexibility that stretch far beyond the boundaries associated, in the widest sense, with the Yoruba.